2023
DOI: 10.1021/acs.chemmater.2c03095
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Doping Induced Phase Transformation in CsPbI3 Nanocrystals with Enhanced Structural Stability and Photoluminescence Quantum Yield

Abstract: The synthesis of air-stable and cubic phases of all-inorganic halide perovskite nanocrystals (HPNCs) by a hot-injection approach is still challenging due to their rapid in situ phase transformations. Therefore, understanding and preventing this phase conversion by doping of cations is the key to improve the structural stability, environmental durability, and photoluminescence quantum yield. Here, the doping of divalent Cu ions at the Pb-site of cesium lead iodide (CsPbI3) is reported to achieve cubic-phase (α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Figure 1d shows the selected area electron diffraction (SAED) patterns of pristine CsPbI 3 NCs, where the diffraction spots associated with the (110) and (130) crystal planes along the [002] zone axis correspond to the orthorhombic phase of CsPbI 3 , consistent with the X-ray diffraction (XRD) and HRTEM results. 28 However, we also observed some additional diffraction spots marked by red circles, which are difficult to index, probably because of the orientation of some NCs in different directions or their overlap with each other. Figure 1e shows the HRTEM image of a single Cu-doped CsPbI 3 NC with an average size of 30 ± 5 nm, indicating increased NC size due to enhanced stability on doping.…”
Section: Atomic-scale Observation Of As-synthesizedmentioning
confidence: 81%
See 2 more Smart Citations
“…Figure 1d shows the selected area electron diffraction (SAED) patterns of pristine CsPbI 3 NCs, where the diffraction spots associated with the (110) and (130) crystal planes along the [002] zone axis correspond to the orthorhombic phase of CsPbI 3 , consistent with the X-ray diffraction (XRD) and HRTEM results. 28 However, we also observed some additional diffraction spots marked by red circles, which are difficult to index, probably because of the orientation of some NCs in different directions or their overlap with each other. Figure 1e shows the HRTEM image of a single Cu-doped CsPbI 3 NC with an average size of 30 ± 5 nm, indicating increased NC size due to enhanced stability on doping.…”
Section: Atomic-scale Observation Of As-synthesizedmentioning
confidence: 81%
“…In our previous work, we observed that doping Cu atoms in CsPbI 3 can enhance its stability, even under laboratory-ambient conditions . In this study, Cu-doped CsPbI 3 NCs with enhanced structural stability at room temperature have been used to investigate the effect of electron beam irradiation while probing single NCs at doses conventionally used in atomic-resolution TEM analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CsPbX 3 perovskite family, CsPbI 3 is especially prone to moisture so that it loses its structural integrity even at room temperature and under moderately humid conditions, causing undesired transformation to the orthorhombic γ-phase and finally degradation to the non-perovskite δphase. [14,15] In the thermally-annealed perovskite films, the α-CsPbI 3 is known to be stable at above 320 °C due to the strain generated at the film/substrate interface caused by thermal expansion mismatch. [16,17] Steele et al reported that the mechanical stress caused by the biaxial anisotropy near the substrate clamping led to a fast phase change (from α!β!γ) during the cooling process of the thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach that has been identified to stabilize the photoactive phase of CsPbI 3 is by partial substitution of the B site occupied by Pb 2+ with some smaller radius elements such as Ca 2+ , Mn 2+ , Ge 2+ , Cu 2+ , Eu 2+ , Bi 3+ , , Sn 2+ , Zn 2+ , Mg 2+ , and Sr 2+ , or by partial substitution of the X site occupied by I – with some smaller radii halide like Br – and Cl – In addition to tuning the tolerance factor, other effective ways of stabilizing the photoactive phase of CsPbI 3 is by reducing the crystallite size in the nanometer range and introducing strain. , …”
Section: Introductionmentioning
confidence: 99%